Development and evaluation of a training program in peer support for former consumers. - Meehan, T; Bergen, H; Coveney, C; Thornton, R (2002)
While mental health policy in Australia promotes the involvement of mental health consumers in service planning, implementation and evaluation, little has been reported on the training required for the new roles that consumers are being expected to undertake. In this study, 10 former consumers of mental health services participated in a 16-week training program in peer support. The impact of the program on the psychological well-being of the participants was assessed using a battery of self-evaluation questionnaires and focus group interviews. Findings suggest that exposure to people with acute mental health problems (i.e. inpatients), did not, in this instance, adversely impact on the psychological well-being of the participants. Barriers to consumer participation in the mental health field are discussed and recommendations for the content and structure of future consumer peer support training initiatives are proposed.